Improvement of Wastewater Treatment Using Lagoons Technology - Awad, Ameera Mohamad; Ibrahim, Husham T.; Al-Aboodi, Ali H. (Basrah Journal for Engineering Sciences, 2023)
Wastewater lagoons have proven to be an economically and environmentally beneficial alternative to traditional methods for treating sewage because of their unique properties, which include simplicity of use and inexpensive construction, energy, and maintenance costs. It is a natural wastewater treatment process that exploits the interactions between bacteria, algae, and other microorganisms and their surroundings to remove pathogens, organic matter, suspended particles, phosphates, ammonia, and nitrates. Stabilization lagoons are widely used throughout the world as they have proved to be a perfectly acceptable and satisfactory treatment system, the effluents produced in tertiary lagoons have been used for irrigation and aquaculture in many countries, indicating the high quality achieved during treatment in these units. This aim of this research is to overview the literature on lagoons’ classification, design, and historical development. It also includes a set of relevant pilot and laboratory-scale experiments. As well as a comprehensive review of factors affecting lagoon performance, including sun’s light, DO, pH, temperature, and nutrients. The relationship between these factors and their use in efficient contaminant removal is also discussed.